THE USE OF MIXED BIOSOLIDS COMPOST AND SOIL AS AGIRICULTURAL MEDIA FOR PEPPER PRODUCTION - AL-Janabi, A. S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in two phases included, production of high quality composts from Bio solids, and the enrichment of this compost through mixing the waste with buffalo, poultry and sewage sludge at ratios of 1: 3 of each and 1: 1: 1: 2 one of them the decomposition and curing process was completed during 14 weeks. Chemical, physical and biological characteristics of mature compost as well as its elemental component and its suitability as agriculture media were determined. The results showed that Coliform bacteria and  Salmonella and Shigella did not appear at the end of maturation. Total fungi count continued to increase to end of maturation when temperature fell to 30 °C. The second phase of the study included, a biological experiment of pepper at plastic house.The experiment included 24 treatment representing six cultural mediums , mixing with soil and fertilizers application. The results of biological experiment revealed that the use of organic media and their mixing with soil or chemical fertilization, led to a significant increase in plant height number of branches per plant, dry matter weight, the concentration of nitrogen, phosphorus and potassium in plant leaves, as well as the increase of early and total yield of pepper fruit compared with the soil alone.Mixing of municipal waste with poultry manure at 1:3 was the best among other mixtures. The use of mixed media with the soil at ratio1: 1 on the basis of size with half of the recommended amount of chemical fertilizer gave the best results in vegetative parameters and fruits yield compared with the use of organic media alone or using the recommended does of chemical fertilizer alone.